ProTEK PSB coating as an alternative polymeric protection mask for KOH bulk etching of silicon - Ab Rahim, Rosminazuin; Bais, Badariah; Yeop Majlis, Burhanuddin; Sugandi, Gandi (Springer, 2013)
The utilization of a newly developed photosensitive polymeric coating, ProTEK PSB plays a signiﬁcant role in realizing simple process steps in the fabrication of MEMS devices using bulk micromachining technology. The photosensitive coating which serves as an alternative to the conventional silicon nitride mask of bulk potassium hydroxide (KOH) etching in devising MEMS devices, particularly in suspended microcantilever structure, is reported in this study. Although the polymeric coating ProTEK PSB acts as an excellent outer protective layer from any pinhole issues, the coating’s lateral etching in the KOH solution is dominant, which results in an undercut problem. Therefore, few investigations have been carried out to identify the most suitable condition for the ProTEK PSB deposition on Si substrate. Initial investigation was done on the effect of Si surface modiﬁcation on the stability of the ProTEK PSB in KOH etching. It was observed that the surface treatment may reduce the undercut ratio for a short period of KOH etching. However, for the extended hours, the surface treatment is not effective enough to improve the stability of the polymeric coating. Therefore, combinations of ProTEK PSB on three substrates were studied in order to obtain a minimum undercut to etch depth ratio of the polymeric coating in KOH bulk etching. The study showed that the combination of ProTEK PSB patterned on thermal oxide results in the most effective etching condition attributed by minimum undercut ratio. Further investigation was carried out on the effect of the KOH etching concentration on the stability of the ProTEK PSB coating over the long hours of bulk etching process. Three concentrations of KOH etchants, KOH 20 wt%,KOH 45 wt% and KOH with isopropyl alcohol (KOH+IPA) were investigated. The results showed that the stability of the polymeric coating was excellent in KOH 20 wt% concentration with a very minimal undercut ratio of 0.05–0.07. In conclusion, the utilization of the polymeric coating ProTEK PSB serves as an alternative etch mask in KOH wet etching which offers simpler and cheaper device fabrication in bulk micromachining technology.